3(2x+5)+5(x-1)=-1

Simple and best practice solution for 3(2x+5)+5(x-1)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+5)+5(x-1)=-1 equation:


Simplifying
3(2x + 5) + 5(x + -1) = -1

Reorder the terms:
3(5 + 2x) + 5(x + -1) = -1
(5 * 3 + 2x * 3) + 5(x + -1) = -1
(15 + 6x) + 5(x + -1) = -1

Reorder the terms:
15 + 6x + 5(-1 + x) = -1
15 + 6x + (-1 * 5 + x * 5) = -1
15 + 6x + (-5 + 5x) = -1

Reorder the terms:
15 + -5 + 6x + 5x = -1

Combine like terms: 15 + -5 = 10
10 + 6x + 5x = -1

Combine like terms: 6x + 5x = 11x
10 + 11x = -1

Solving
10 + 11x = -1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 11x = -1 + -10

Combine like terms: 10 + -10 = 0
0 + 11x = -1 + -10
11x = -1 + -10

Combine like terms: -1 + -10 = -11
11x = -11

Divide each side by '11'.
x = -1

Simplifying
x = -1

See similar equations:

| 7(x-1)-2(x-2)=3 | | 2(3x+8)-3(x-2)=25 | | 6x-5(4x+13)=33 | | 11x-1=3(3x-5) | | 7(3-x)+9x=26 | | 8(3x+2)=4(5x+1) | | 2(4x-5)= | | 7x+6=2(3x+2) | | 4(5x-1)=3(4x+12) | | 2(3x+5)-3=16 | | 3(8x+2)-4x=36 | | 3x+4(2x-3)=10 | | 9x+2(x+7)=36 | | 7(5x-2)-8(4x+1)=5 | | 6(4X+3)-9(2X+1)=21 | | 3(3X+5)+2(3X-7)=19 | | 3(9X+4)=5(5X+4) | | 5(7X-1)=11(3X+2) | | 100-96=31y-35y | | 6(3X+2)=4(4X+7) | | -14m+8m=6-60 | | 9p+5q=63 | | 0=-9t | | 3(X+0.3)=1-X | | 3t+9t=20-10+26 | | 3x+14x-5=0 | | 7(a+3)=49 | | 3(a-1)=2(a+1) | | 13-13=2w-w | | -97-10x=9x+7 | | 7=7c-7 | | 3x+7=-45+10x |

Equations solver categories